AIAC : Associazione internationale di archeologia classica - International Association for Classical Archaeology (2003)
[Dt.:] Informationen zu Vorträgen, Konferenzen und sonstigen Veranstaltungen der Organisation, neuere Nachrichten und Jahresberichte seit 2003. Überdies einen Online-Newsletter der Jahre seit 2003. - [Engl.:] Information on lectures, conferences and other events of the organisation, news and annual reports since 2003. Also an online newsletter since 2003.